Meritocracy, excellence and school exclusion: A scoping review - Ferreira, Marylin Regal (2023)
School meritocracy is a system for rewarding students with benefits assumed for motivation and recognition of effort, but also with a negative dimension associated with the intensifica-tion and stratification of inequalities. Thus, the main objective of the present study is to analyze the literature on school meritocracy and the logics of action of schools in this context. The method used is a scoping review, aimed at selecting, analyzing and synthesizing the literature found in four databases: Web of Science, Scopus, RCAAP and Google Scholar. The results show a need for reflection on the concepts of school justice and exclusion, associated with meritocratic ideology in the logic of equal opportunities.